Plot size misperceptions and soil health: A New research agenda - David M.A. Murphy; Andrew M. Simons; Pieter Pypers; Meklit Chernet; Dries Roobroeck (Soil Security, 2023)
Farmer misperceptions of plot size can potentially lead to greater than intended levels of fertilizer use, which can increase the threat of soil fertility decline and non responsiveness of crops to inorganic fertilizer application. In addition, due to diminishing marginal returns of fertilizer use on grain yields, overestimation of plot size can potentially decrease fertilizer profitability. In this study, we use data collected from randomly selected farmers in rural western Kenya that include both the estimated sizes of the agricultural plots as reported by the farmers and their GPS-measured sizes. We find that 65 percent of plots are overestimated by at least 20 percent. We also find that inorganic nitrogen use is strongly increasing in plot size misestimation: a 10% increase in plot misestimation was associated with a 2.6 percent increase in commercial nitrogen application. Next, we build a random forest model to examine the agronomic efficiency of the farmer intended fertilizer use rates vs. actual rates. We find that misestimation of plot sizes is associated with an average decrease in return on investment of 5% (12%) at application rates of 60 kg N/ha (120 kg N/ha). Building on this exercise, we review the literature linking soil health and plot size misperceptions and conclude by proposing a new research agenda to examine how plot size misperceptions affect soil health and farmer well-being, more broadly.